Selection of Soil and Water Conservation Technologies and Native Tree Species for Rehabilitation of Degraded Arid Lands in Southeast Ethiopia - Abeje Eshete; Shambel Teshome; Aliyi Edaso; Getaw Yilma; Gemedo Furo (International Journal of Forestry Research)
The large-scale commercial agriculture, mining, expansion of sedentary agricultural settlements, and overgrazing in Ethiopian pastoral areas have become a major cause of land degradation. Such activities reduce grazing capacities and impoverish already fragile living conditions of the pastoralists. Such an increase in land degradations necessitates urgent calls for interventions. The main objectives of this study were to select the best performing soil and water conservation technologies and native tree species to restore degraded lands of arid and semiarid conditions in Liben District of Guji Zone, Oromia Reginal State, Ethiopia. Four locally grown and locally preferred tree species, namely, Cordia africana, Acacia tortilis, Acacia goetzei, and Combretum molle, were planted in five soil and moisture conservation structures (control, half-moon, spot hoeing, mowing, and trench). The survival rate and height and root collar diameter (RCD) growth of planted tree species were collected two years after planting. A significantly higher survival rate, RCD, and height growth of planted seedlings were recorded from half-moon (52.44 ± 12.48%; 1.66 ± 0.31 cm; 51.57 ± 2.79 cm) and trench (64.00 ± 11.49%; 1.92 ± 0.27; 69.67 ± 2.62 cm) moisture conservation structures, respectively. Acacia tortilis (58.22 ± 12.38%) and Acacia goetzei (42.99 ± 8.81%) had better survival rate than Cordia africana (4.00 ± 1.91%) and Combretum molle (24.22 ± 7.34). Cordia africana attained the largest RCD (2.50 ± 0.34 cm) and height (95.83 ± 17.25 cm) growth, followed by Acacia tortilis and Acacia goetzei. It is concluded that Acacia tortilis and Acacia goetzei are better species to grow in degraded lands. The half-moon and trench moisture conservation structures have a great potential for degraded areas of the arid and semiarid conditions of Ethiopia for better tree establishment, survival, and enhanced growth thereby rehabilitation of degraded lands.